Service quality measurement: implications for healthcare sector in Bulgaria. (2015) - Vassileva, Bistra; Balloni, Antonio José
The aim of the paper is to present the service quality situation in hospitals in North-Eastern Planning Region in Bulgaria. Our intention was to assess the gap between the expected and perceived healthcare service quality in hospitals. To meet these goals we conducted a study using prospective questionnaire provided by the GESITI project [management of system and information technology in hospitals (GESITI, 2013a)] and SERVQUAL scale. The results helped us to summarise the challenges for Bulgarian hospitals to diminish the 'quality gap' as well as to identify the critical factors for achieving high quality level of healthcare services. Several recommendations and implications for future research are defined at the end of the study.